Bayesian Analysis of the Association between Casein Complex Haplotype Variants and Milk Yield, Composition, and Curve Shape Parameters in Murciano-Granadina Goats - Inostroza, María Gabriela Pizarro (Animals (Basel), 2020)
SIMPLE SUMMARY: Although the casein complex has been reported to condition economically important traits in dairy species, information in goats is scarce. The analysis of haplotypic sequences has been suggested to maximize the results obtained after the assessment of other genetic units, such as SNPs. We studied the association between haplotype sequences for αS1-, αS2-, β-, and κ-casein loci and milk yield, protein, fat, dray matter, lactose, somatic cells count, and the curve shape parameters that they describe during lactation (peak and persistence). This aimed to provide basic research data for the integration of haplotype monitoring in the selection strategies of dairy goats. ABSTRACT: Considering casein haplotype variants rather than SNPs may maximize the understanding of heritable mechanisms and their implication on the expression of functional traits related to milk production. Effects of casein complex haplotypes on milk yield, milk composition, and curve shape parameters were used using a Bayesian inference for ANOVA. We identified 48 single nucleotide polymorphisms (SNPs) present in the casein complex of 159 unrelated individuals of diverse ancestry, which were organized into 86 haplotypes. The Ali and Schaeffer model was chosen as the best fitting model for milk yield (Kg), protein, fat, dry matter, and lactose (%), while parabolic yield-density was chosen as the best fitting model for somatic cells count (SCC × 103 sc/mL). Peak and persistence for all traits were computed respectively. Statistically significant differences (p < 0.05) were found for milk yield and components. However, no significant difference was found for any curve shape parameter except for protein percentage peak. Those haplotypes for which higher milk yields were reported were the ones that had higher percentages for protein, fat, dry matter, and lactose, while the opposite trend was described by somatic cells counts. Conclusively, casein complex haplotypes can be considered in selection strategies for economically important traits in dairy goats.